Asymmetric Sharpless epoxidation of 13Shydroxy-9Z,11E-octadecadienoic acid (13S-HODE) - Omar, Muhammad Nor; Moynihan, Humphrey A; Hamilton, Richard J. (Wiley, 2003)
The asymmetric Sharpless epoxidation of methyl 13S-hydroxy-9Z,11E-octadecadienoate (13S-HODE, 1) with tert-butyl hydroperoxide (TBHP) catalysed by titanium tetraisopropoxide {Ti(iOPr)4} in the presence of L(+)-diisopropyl tartrate (L-DIPT) gave methyl 13S-hydroxy-11S,12S-epoxy-9Z-octadecenoate 2 (erythro isomer) in 84% diastereomeric excess (de). The epoxidation of 1 with TBHP catalysed by Ti(iOPr)4 in the presence of D(-)-DIPT yielded methyl 13S-hydroxy-11R,12R-epoxy-9Z-octadecenoate (threo isomer) 3 in 76% de.